2021
DOI: 10.1016/j.lmot.2020.101693
|View full text |Cite
|
Sign up to set email alerts
|

Liking as far as you like yourself: Exploring the Self-Referencing effect across multiple intersecting regularities and its relationship with self-esteem

Abstract: Classic instances of evaluative learning require the spatio-temporal contingency between source and target stimuli. However, people can learn to like stimuli in a more indirect fashion. Moreover, many of our preferences are self-referential: we tend to like the objects that are related to ourselves. For instance, it is demonstrated that performing the Self-Referencing task, a categorization task based on intersecting regularities between the self and a target stimulus, results in a transfer of positivity from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This task may have given participants with high SPQ scores the opportunity to express the variety of their social drives. This may have made the task more attractive and motivating for them than for low SPQ scorers 73 , 74 . These surprising results are in fact consistent with clinical observations that patients with schizophrenia tend to pay more attention to, and process more quickly, materials that may be associated with delusional beliefs/ideations.…”
Section: Discussionmentioning
confidence: 99%
“…This task may have given participants with high SPQ scores the opportunity to express the variety of their social drives. This may have made the task more attractive and motivating for them than for low SPQ scorers 73 , 74 . These surprising results are in fact consistent with clinical observations that patients with schizophrenia tend to pay more attention to, and process more quickly, materials that may be associated with delusional beliefs/ideations.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with other-referencing, self-referencing has been acknowledged as a more effective strategy to boost memory (Yin et al, 2019). Recent research has argued that the self-referencing task, which examines the relatedness between the self and a target stimulus, tends to result in a transfer of positivity from the self to the target (Mattavelli et al, 2021). Prior research has indicated that information is more persuasive when it is relevant to the audiences (Debevec & Iyer, 1988).…”
Section: Self-referencingmentioning
confidence: 99%